VD_FINDINFO HC / 2020 / 869 vom 13. November 2020 - VD Tribunal cantonal (2020)
DROIT DES SUCCESSIONS, EXÉCUTEUR TESTAMENTAIRE, INTERDICTION D'ALIÉNER | 518 CC, 256 al. 2 CPC (CH), 261 CPC (CH), 262 CPC (CH), 59 CPC (CH)